Influence of freezing and thawing on drainage behaviour for porous asphalt pavement based on molecular dynamics simulation. Issue 14 (6th December 2022) - Yu, Tengjiang; Zhang, Haitao; Sun, Junfeng; Chen, Dan; Wang, Haomin; Feng, Yuping
ABSTRACT: To explore the influence of freezing and thawing on drainage behaviour for porous asphalt pavement (PA), molecular dynamics simulation was applied to study the interaction between asphalt and water. Based on the establishment and verification of micro models for asphalt (virgin and aged) and water (ice, ice–water mixture and water), the micro behaviour of interfacial transition zone was intuitively observed. Combined with the multi-gradient experiment results, the micro influence mechanism of freezing and thawing on drainage behaviour of porous asphalt pavement was revealed. The results show that the interaction energy of asphalt–water changes with the occurrence of freeze–thaw. The interaction energy (attraction) between aged asphalt and water is enhanced, which leads to water-induced distress more easily. In addition, with the occurrence of freeze–thaw, the relative concentration of hydrogen atoms at the interfacial transition zone gradually increases, while the fluctuation of carbon atoms increases. The results provide a micro-mechanism for the study of drainage behaviour of porous asphalt pavement under freezing and thawing, which has certain theoretical significance and practical value.